Adoption of Dairy Farming Technologies by the Farmers of Nagaur District of Rajasthan - S. R., Kumawat; M. P., Verma, (Indian Journal of Extension Education, 2016)
The present study was conducted in Nagaur district of Rajasthan to know the adoption level of farmers regarding dairy  farming technologies. In all 180 farmers were selected randomly from three block of the Nagaur district. The result of the  study indicated that adoption level of farmers regarding improved breed of buffalo (45 %), Dry fodder (86 %) feeding of  concentrate during lactation (45%) chaffing of fodder (58 %) colostrums feeding to newly born calves (47 %), and  drinking water (72%) were quite high. The adoption of dairy farming technologies was positively and significantly related  with thirteen independent variables viz. Age, Education, Family size, dairy experience, organization participation, land  holding, livestock possession, annual income, economic motivation, market orientation, scientific orientation and  knowledge of improved dairy management practices at 0.01 level probability.
Keywords: Adoption; dairy management practices